Manufacturers’ views on outcome-based agreements - Sahar Barjesteh van Waalwijk van Doorn-Khosrovani; Lonneke Timmers; Anke Pisters-van Roy; Joël Gijzen; Nicole M.A. Blijlevens; Haiko Bloemendal (Journal of Market Access & Health Policy)
Introduction: utcome-based agreements (OBAs) are occasionally deployed to relieve the burden of high drug prices on healthcare budgets. However, it is not clear when manufacturers are willing to collaborate in establishing such agreements. Therefore, we explored the feasibility of OBAs from the manufacturer’s point of view. Methods: Dutch market-access experts from eight major pharmaceutical companies, globally active in the field of oncology, were interviewed. Opinions were compiled, and interviewees and their colleagues were then given the chance to review the manuscript for additional comments. Results: Most interviewees believe that OBAs can be useful in providing access to off-label use of authorised medicines, especially when no alternative treatment is available for seriously ill patients. For the licenced indications, manufacturers seem to be more inclined to collaborate when there is a potential incentive to improve market-access (e.g., if the product is not used because of concerns regarding its effectiveness). However, manufacturers are less likely to collaborate when there are greater financial risks for the company. Further concerns were definition of outcome or performance, the impact of compliance on the effectiveness of a drug, administrative burden, uncertainty regarding revenue recognition and the challenges of reimbursing combination therapies. Discussion: Market-access interviewees were generally positive about OBAs, however they were more reluctant towards OBAs for registered indications with low response-rate. The definition of performance or outcome and its clinical relevance and validity, the feasibility of OBAs and their administrative burden are relevant aspects that need to be addressed in advance. Ideally, countries should collaborate to share the outline of OBAs and create shared databases to accumulate evidence.